Gravity-fed Combined Solar Receiver/Storage System Using Sand Particles as Heat Collector, Heat Transfer and Thermal Energy Storage Media. (May 2015) - Iniesta, A. Crespo; Diago, M.; Delclos, T.; Falcoz, Q.; Shamim, T.; Calvet, N.
Abstract: An innovative gravity-fed combined solar receiver/storage system for thermal energy storage (TES) is presented for concentrated solar power (CSP) plants with beam down tower configuration. Sand particles are employed as heat collector, heat transfer and thermal energy storage media in contrast to conventionally used materials such as molten salts or synthetic oils. Relevant properties of two sand samples from the United Arab Emirates (UAE) deserts are examined. A prototype of the receiver was manufactured and its elements were characterized. Preliminary tests on the prototype were performed under the concentrated flux of a 2 kW solar furnace and associated results are presented.